Feitiçarias e magias: mulheres negras e as visitas pastorais na Capitania de São Paulo – séc XVIII - Salomé de Souza, Alexandre Bueno (2016)
This research is dedicated to the study of witchcraft, in colonial Brazil in the mid-seven hundred, by Colonial Brazil, having as main sources the inquisitorial documentation referring to the colonial period. In this work, we will focus on the analysis of cases of magic and witchcraft practices carried out by black women and our thematic focus focuses on specifically Portuguese magical beliefs and practices, having as a theoretical contribution the accounts of the history of mentalities and their cultural representations. This research also aims to analyze the black woman in relation to her religiosity. Throughout our research, we can observe women throughout the historical periods, relating periods and places, observed in their religious culture brought to Brazil. However, this work is relevant in the field of historiography, in the face of the prejudice that black women have suffered throughout history in relation to their creeds and beliefs, often interpreted as witchcraft and magic. This theme will also demystify the relationship of witchcraft practices with the cults of Afro-Brazilian religions, showing the vision and profile of black women in colonial Brazil. The research may be useful for society and for Brazilian History scholars to understand colonial society, knowledge about the role of women and for scholars of the Sciences of Religion to favor understanding of the religiosity of the Brazilian colonial period, collaborating for the development of studies against intolerance.